RELATIONSHIP OF SAFE RIDING KNOWLEDGE, PERCEPTION ABOUT DANGER, AND SAFE RIDING BEHAVIOR AMONG SENIOR HIGH SCHOOL STUDENTS IN SAMARINDA INDONESIA - Setyowati, Dina Lusiana; Firdaus, Ade Rahmat; Rohmah, Nur Rohmah (YCAB Publisher & IAKMI SULTRA, 2019)
Background: A traffic accident is a major factor of death of young people, especially in males, and those with physical disabilities. Although there was a decrease of the number of traffic accidents in 2014 (1,094 accidents) compared to a previous year (1,041 accidents), however it still remains high. Objective: This study aimed to identify the relationship of safe riding knowledge, perception about danger, and safe riding behavior in high school students in Samarinda City, Indonesia.Methods: The study employed a survey with cross sectional approach in 315 students. Data were collected using questionnaires to measure safe riding knowledge, perception about danger, and safe riding behavior. Data were analyzed using Chi square with Î± .05.Results: The results showed that there was a significant relationship of safe riding knowledge, perception of danger, and safe riding behavior in high school students (p <.05).Conclusion: This finding provides the insights to reduce traffic accidents in high school students increasing the knowledge and perception of safe riding by highlighting the involvement of parents, teachers and related institutions.